A framework development for correlation between employee social skills and employability factors - Nor Shela Saleh,; Mohd Shafie Rosli,; Khairunesa Isa,; Thuaibah Abu Bakar,; Azlah Md. Ali, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Employability is an issue that frequently comes up for everyone involved, particularly those soon to graduate. Work competitiveness, a shortage of work offers, on-the-job incompetence, and compensation from employers and organisations that is disproportionate to their acceptability are all issues. Its graduates have a constrained and concerned perception, especially if they are required to repay a student loan. This study requires determining one of the traits impacting graduate employability: employee social skills. Communication skills, decision-making skills, and negotiating skills are the three key domains of employee social skills that employers prioritise most strongly. These three components have been identified by researchers as having an impact on employability in a group of career factors, organisational factors, and individual factors. Due to prior studies and approximately national agenda provision, researchers produced a model framework titled "A Framework for Correlations Between Employee Social Skills and Employability: Factors.".